THE CONTRIBUTION OF MISSIONARIES TO THE ABOLITION OF SLAVERY IN SOUTH TRAVANCORE (International Journal of Food and Nutritional Sciences, 2022)
South Travancore is in Kerala in India. It includes the districts of Kollam Trivandrum and Kanyakumari. In South Travancore origin of slavery was closely associated with the inception of the caste system which in turn was based hierarchical social order. Slavery was officially recognised in this area. The lowest section in the society was the slave caste. In their movements among the common people, the missionaries came to know the pitiable condition connected with the slavery that existed in South Travancore and the miserable condition of the slaves. Missionaries presented a memorandum on the lamentable plight of the slaves to king Uttram Thirunal Marthanda Varma through Resident. It made the king to issue the proclamation of 1855 by which slavery was legally abolished.